An improved sine–cosine algorithm for simultaneous network reconfiguration and DG allocation in power distribution systems - Raut, Usharani; Mishra, Sivkumar (Applied soft computing, 2020)
This paper presents a recently proposed meta-heuristic sine–cosine algorithm combined with levy flights to reconfigure the distribution network with simultaneous allocation (placement and size) of multiple distributed generators (DGs). The algorithm is proposed to be adaptive with an exponentially decreasing conversion parameter and a self-controlled levy mutation in order to explore the solution space more efficiently during the course of iterations. The effectiveness of the algorithm is verified on 10 standard benchmark functions. Later, it is used to address the issues of a real combinatorial optimization, such as network reconfiguration (NR) in the presence of DGs. In order to enhance the effectiveness of the system, a multi-objective function is developed considering total active power loss and overall voltage stability of the network with suitable weights without violating the system limitations. To evaluate the objective function, a depth fast search integrated forward–backward sweep based load flow technique that is capable of managing any topological alterations owing to the NR and DG integration is developed. In order to demonstrate the efficiency of the system, four distinct cases of NR and DG installation are investigated. The proposed algorithm is contrasted with other well-known algorithms that exist in the literature, namely, harmony search algorithm (HSA), fireworks algorithm (FWA), genetic algorithm (GA), refined genetic algorithm (RGA) and firefly (FF) algorithm considering 33 and 69-bus distribution systems at three different load levels and its superiority is established. •Applications of ISCA to solve the issues of simultaneous NR and DG allocation.•Incorporation of self adapting levy mutation strategy to basic SCA.•Development of a DFS integrated FBS based load flow method.•Validation of the algorithm on 33 and 69-bus distribution systems.•Comparison of effectiveness of ISCA with well known competitive algorithms.